Trends and technologies of video coding - Jiantong ZHOU; Haitao YANG; Dong LIU; Xiang MA; Tian WANG (Dianxin kexue)
The current video coding uses block based hybrid architecture,which uses predictive,transform,quantization and entropy coding techniques to efficiently compress video signals.Further optimizations on current architectures provide more flexible processing and coding for local characteristics of video image signals.Video coding based on machine learning was expected to change the existing hybrid coding framework partially or comprehensively,and bring new research ideas to video coding.In addition to existing 2D video signal,the future of video also needs to spherical video coding and volumetric video coding for AR/VR applications,the new video source data format of the video encoding technology has brought new opportunities and challenges.